Prediction of Indian droughts with lower stratospheric winds - THAPLIYAL, V. (MAUSAM, 1984)
An extremely deficient summer monsoon (June to September) produces severe drought conditions in India because 75 per cent of the annual rainfall over a large part of the country occurs, during this season. The prediction of large scale monsoon failure sufficiently in advance can therefore help to forecast the occurrence of drought over India. A number of studies have indicated that the Quasi Biennial Oscillation (QBO) plays an important role in linking different layers of the atmosphere. Recently, Thapliyal 0979) bas shown that mean January circulation features at 50 mb level are able to indicate the deficient monsoon rainfall in westerly QBO years. This however does not explain fully the large scale monsoon rainfall that occurs in westerly QBO years such as 1979. An attempt has therefore, been made here to identify a few global circulation features during antecedent months which can be, used, for predicting large scale monsoon failure over India. For this purpose, the mean monthly global circulation features in the lower stratosphere have been studied for two recent years of contrasting monsoon over India, namely, 1980- a good monsoon year, and 1979- a severe drought year. During these two years, completely different circulation features have been found at 50 mb level. In winter1980 a subtropical ridges situated over the northern hemisphere around latitude 20 deg. N. On the other hand, in winter 1979 three significant large; scale circulation features are situated over the globe. The prominent among them is a pair of trough and ridge which runs parallel to the equator and is mostly situated in the tropical region pf the northern hemisphere. Simultaneously a near equatorial trough is also found in 1979 which encircles the southern hemisphere. Encouraged by this result, the mean winter circulation features during the recent 16 years (1965 to 1980) have been studied in relation to monsoon rainfall in India. The circulation features like those of winter 1980 are found in all the easterly QBO years while the features like those of winter 1979 .are found in all the westerly QBO years. It has been noted that the location and the extent of the ridge and the trough provide reliable indications regarding the deficient monsoon rainfall in India. Years, when the extent of northern hemispheric ridge and trough is small, are followed by good monsoon rain while years when the extent of these circulation features is large are followed by deficient monsoon rains. This relationship has been expressed by an exact mathematical model which has been successfully used forecasting the large scale rainfall deficiency during the recent monsoon seasons (1965 to 1980). The performance of the forecast model during recent 16 years has been found excellent. From the model it is interred that the winters, in which the mean longitudinal length of the pair of trough and ridge over northern hemisphere is more than 140 degrees longitude are followed by severe drought conditions during subsequent summer monsoon over India. Thus, severe droughts have occurred over India in westerly QBO years only. Based on this method the drought conditions due to large scale monsoon failure could, therefore, be forecast about 3 months prior to the &tart of the season over India.